СПОСІБ УЧИНЕННЯ КРАДІЖОК У СІЛЬСЬКІЙ МІСЦЕВОСТІ ЯК ФАКУЛЬТАТИВНА ОЗНАКА ОБ’ЄКТИВНОЇ СТОРОНИ СКЛАДУ ЗЛОЧИНУ - Лютий, Віталій Віталійович (SUPREMANCE OF LAW, 2018)
The main methods of committing thefts in rural areas are considered in the article. The author draws attention to the personal characteristics of the criminals and to the encroachment of theft in rural areas, which also stipulate ways to conceal the crime and dispose of property. The author also considers tools and means of committing thefts in rural areas.
Keywords: theft; countryside; the objective side of the crime; facultative signs; property